Quantitative AnalysesQuantitative Analyses of the Functional Constituents in SanYangSam and SanYangSanSam of the Functional Constituents in SanYangSam and SanYangSanSam - Il-Soo Shin; Eunbi Jo; Ik-Soon Jang; Hwa-Seung Yoo (Korean Pharmacopuncture Institute, 2017)
Objective:SanYangSam and SanYangSanSam are traditional Korea-medical herbs that are grown from Panax ginseng C.A. Meyer. In our previous studies, we found that the functional compounds in SanYangSam and SanYangSanSam were different and depended on the type and the cultivation environment of ginseng. This study aimed to profile the functional constituents in SanYangSam and SanYangSanSam.Methods:To profile the functional aspects of the many compounds that have therapeutic activities in SanYangSam and SanYangSanSam extracts, we used liquid chromatography tandem mass spectrometry and quadrupole orthogonal acceleration time-of-flight mass spectrometry.Results:A total of four major compounds were detected; two of which were the natural flavonoids kaempferol and quercetin. Among others, two polyacetylene compounds, including panaxydol and panaxynol, were detected.Conclusion:In this study, we found that panaxydol, one of the polyacetylene constituents of ginseng, is a candidate anti-cancer agent in SanYangSam and SanYangSanSam pharmacopuncture. In addition, we found that the panaxydol levels in the SanYangSanSam extract were over 30 times those in the SanYangSam extract.